Internal control systems in West Malaysia's state mosques - Sulaiman, Maliah; Siraj, Siti Alawiah; Mohamed_Ibrahim, Shahul Hameed (Association of Muslim Social Scientists, International Institute of Islamic Thought, 2008)
The embezzlement of funds from religious organizations, particularly in western church institutions, is becoming more common. Such scandals have raised concerns about their internal control systems. Despite the lack of any reported financial scandals in mosques, there is a growing concern as to whether they experience the same deficiencies as other religious institutions do.Our study examines the internal control procedures related to the receiving income and disbursing funds in West Malaysia’s state mosques. A questionnaire survey and informal interviews were used to collect the data. The results indicate that these mosques have a strong internal control system vis-à-vis these two activities. This study also reveals that their practice of several basic control activities (e.g., segregating duties, recording financial transactions, and authorizing particular activities) is satisfactory. Though this is an exploratory study, the results may provide a benchmark for further studies examining internal control practices in religious organizations.